Uma plataforma para suporte à navegação autônoma de veículos aéreos de pás rotativas - Pizetta, Igor Henrique Beloti (2013)
This M.Sc. Thesis has the objective of creating a platform to support the test of simulated and real autonomous flights, using high level controllers for miniature aerial vehicles of the class helicopter. Such platform is designed for use with commercial miniature helicopters and embeds the instrumentation necessary for flying autonomously. Aiming at this, an inertial sensor, an ultrasonic sensor, a barometric sensor and a GPS receptor were integrated to the vehicle. Besides, an electronic board specific to actuate over the servomotors of the helicopter, and to get the data delivered by the onboard sensors the aircraft as well, referred to as the AuRoRa Board, was designed and manufactured. Such board reads all the commands coming from the radio control and the signals coming from the high level controller responsible for the autonomous navigation of the vehicle. The selection of the signal that will actuate over the servos is performed by the operator through the radio controller, for security reasons (manual operation disables the autonomous operation when activated by the operator). In this work it was also used a low level stabilizer, called Helicommand, whose objective is to estabilize the helicopter hovering in its current position, to make easier the control of its navigation and, in the event of communication loss, to keep the helicopter stabilized until either recovering the communication or a human operator takes the vehicle control via radio. It was also implemented a high level Hardware-in-the-Loop platform, called AuRoRa Platform, capable of running simulations and real experiments, these last ones using the AuRoRa Board to actuate over the servomotors of the vehicle. In such platform one can choose among various aircrafts, amongst which are the quadrotors and the miniature helicopters T-REX 450 and T-REX 600 (these two last ones were the aircrafts dealt with in this Thesis). The platform is also capable of supporting various communication channels, like serial, Bluetooth and UDP (User Datagram Protocol), besides accepting different controllers and vehicle models. The platform presents a decentralized characteristic: to avoid overloading a single computer with the control signals synthesis and the online exhibition of the flight data one can distribute certain tasks (e. g., online exhibition of flight data) to another computer, using a UDP communication channel.